Malta : Technical Assistance Report-Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2018)
Malta meets a large number of the principles of the Fiscal Transparency Code at good or advanced level. Based on the assessment made in this report, Malta meets the good or advanced practice on 21 out of 35 principles in the Code. One principle, related to natural resources, was not relevant to Malta and therefore not assessed. Malta meets the basic practice on a further 12 principles (Table 0.1). Practices are stronger in the areas of fiscal reporting and fiscal forecasting and budgeting, where Malta is subject to and complies with the comprehensive reporting framework established by the European Union. Practices are generally weaker in the area of fiscal risk analysis and management, notably oversight of public corporations.